Islamic religious character in inclusive education and its contribution to various characteristics of children with special needs - Anggoro Putranto; Eka Danik Prahastiwi (Journal of Interdisciplinary Islamic Studies, 2023)
Developing the nation's Islamic character education for students with special needs gives value and character to them. So that the implementation of inclusive education is expected to become an education system where children with special needs (ABK) can study in public schools in their school environment and are equipped with support services and education that have been adapted to the abilities and needs of these children. However, it is more focused on their special needs. this is very important to implement, with inclusive education it can provide opportunities and open opportunities for children with special needs (ABK) to obtain education without any discriminatory treatment. This inclusive education is the most suitable learning tool for all children in terms of adaptation and socialization so that it can become a mandatory forum between children to socialize with the diversity that exists. This shows that there is no longer discrimination against children with special needs (ABK) with children who do not have special needs, because all children have the same opportunity to obtain education according to the needs and abilities of each child.